2011
DOI: 10.4103/0976-500x.85958
|View full text |Cite
|
Sign up to set email alerts
|

Olopatadine hydrochloride and rupatadine fumarate in seasonal allergic rhinitis: A comparative study of efficacy and safety

Abstract: Objective:To compare the efficacy and safety of olopatadine and rupatadine in seasonal allergic rhinitis (SAR).Materials and Methods:A 2-week, single-centered, randomized, open, parallel group comparative clinical study was conducted on patients with SAR. Following inclusion and exclusion criteria, 70 patients were recruited and were randomized to two treatment groups and received the respective drugs for 2 weeks. At follow-up, clinical improvement was assessed in terms of change in total and differential coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
6
16
0
Order By: Relevance
“…Other adverse events noted were headache and dryness of mouth which were also found in the previous study. [214] Our study did not reveal any change in electrocardiogram (ECG), supporting the previous studies which also showed no change in ECG findings. [101415]…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Other adverse events noted were headache and dryness of mouth which were also found in the previous study. [214] Our study did not reveal any change in electrocardiogram (ECG), supporting the previous studies which also showed no change in ECG findings. [101415]…”
Section: Discussionsupporting
confidence: 90%
“…Symptom severity was determined by the TNSS which consisted of sneezing, rhinorrhea, itching, and nasal congestion scored on a severity scale from 0 to 3 (0 = none, 1 = mild, 2 = moderate, and 3 = severe), such that the maximum possible TNSS was 12. [28]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in eosinophil count is the hallmark of late phases of allergic diseases. The scrupulous control of this parameter is an important therapeutic aim . Previous research found a greater reduction in eosinophil count with rupatadine compared with cetirizine, which suggests the superiority of rupatadine .…”
Section: Discussionmentioning
confidence: 88%
“…The scrupulous control of this parameter is an important therapeutic aim. 21 Previous research found a greater reduction in eosinophil count with rupatadine compared with cetirizine, which suggests the superiority of rupatadine. 22 Decreases in differential eosinophil count, TLC, and differential neutrophil count were revealed, whereas no significant differences in differential monocyte and basophil counts were seen in the rupatadine group.…”
Section: Discussionmentioning
confidence: 95%